Sistem Temu Kembali Informasi Pasal-Pasal KUHP Menggunakan Metode Cosine Similarity dan Pembobotan Inverse Book Frequency - Billy Sabilal; Mochammad Ali Fauzi; Indriati Indriati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Indonesia law based on the Kitab Undang-undang Hukum Pidana (KUHP) is a matter that must be obeyed as a people or related in their field, such as the police, judges or people associated with the trial. Kitab Undang-undang Hukum Pidana contains 569 pasal in the book that will be very inefficient and practical if you have to take it and also if you want to find related articles that have to open pages one by one manually. Based on these conditions the application developed an application using the cosine similarity method and weighting inverse book frequency. Cosine similarity method is used to calculate the similarity or proximity of article documents to queries. Weighting inverse book frequency weighting terms that consider the distribution of book collections. The value of each term is assumed to have a proportion opposite to the number of books containing that term. The performance of the system is indicated by the results of testing on each variation of 10 queries by dividing 3 1-word queries, 3 2-word queries, 3 3-word queries and 1 4-word queries tested, with performance precision values of 0.5273, recall 1, f.measure 0.6063 while the best precision@k results in the third rank of 0.6498.